THE STATE OF CARBOHYDRATE AND LIPID METABOLISM IN OBESE PATIENTS AFTER BILIOPANCREATIC BYPASS SURGERY (International conference on multidisciplinary science, 2025)
The paper presents material on the problem of surgical treatment of patients with severe forms of obesity. Based on factual material, an assessment is given of the methods of combined bariatric operations used by the authors.